Hunting Hackers. A gift from the ‘mute guest’ - Martínez-Cazalla, María Dolors (Revista de Humanidades de Valparaíso, 2018)
We can be hacked because there are not indiscreet questions but there are imprudent answers. The main aim of this paper is actually to learn how to create the best possible answers, the most prudent ones, in order to remain as safe as we can. That is what Hunting Hackers means: to think about what piece of information was relevant for the hacker and why that one in particular and not another. If we could preview our flaws then we would be able to keep our zone safer from hackers. In order to reach this objective, we will analyse how the cryptic language known as Russian Cards operates. This study does not intend to show how the cryptic language is broken into, but to take advantage of the learning gifted in knowing the flaw itself. It is precisely in the learning of the flaw that we can find the answer to what and why we may be hacked. In proportion to the amount of flaw information at our disposal, we will be able to hunt hackers: to stop them completely or, at least, to weaken a possible hacker attack.